Pengaruh Sinar Plasma Terhadap Peningkatan laju Perkecambahan Bawang Merah (Allium ascalonicum L.) Asal Biji TSS Varietas Sanren F1 - Mukhammad Akmal Surur; Erma Prihastanti; Sri Widodo Agung Suedy; Endah Dwi Hastuti; Sri Darmanti (Jurnal Penelitian Pertanian Terapan, 2024)
ABSTRACT Sanren F1 shallot is a type of TSS variety that is widely cultivated by Indonesian onion farmers. The cultivation of Sanren F1 shallots is faced with the constraints of non-uniform germination and low seed viability, thus affecting seed quality and yield of TSS shallots. Plasma light radiation is one of the fast, economical and pollution-free plant breeding methods to improve seed performance and yield. This study aims to determine the effect of plasma light period on the germination rate of shallots from TSS seeds of Sanren F1 variety. The research design used was a single-factor Completely Randomized Design (RAL). The factor used is the irradiation period with 6 levels, namely: P0 (control), P1 (5 minutes radiation), P2 (10 minutes radiation), P3 (15 minutes radiation), P4 (20 minutes radiation), and P5 (25 minutes radiation). The variables observed were germination power, germination rate, seed vigor and sprout height. The data obtained were analyzed using Analiysis of Variance (ANOVA) at 95% confidence level for the formation of the results significantly influenced or not. If influential then continued with Duncan's Multiple Range Test (DMRT). The results showed that plasma light treatment at the irradiation level of 15 minutes (P3) gave a real effect on the growth parameters, namely germination height and was able to increase the germination and seed vigor to 100%. Keywords: Shallot, Germination, Plasma radiation, TSS